PENGARUH TEKNIK SELF CONTROL TERHADAP PERILAKU KECANDUAN INTERNET SISWA DI SMKN 1 PEKANBARU - Sri Noviarti Rusdi; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of self control techniques on internet addiction behavior of students of SMKN 1 Pekanbaru. This type of research is a quantitative study with an experimental method using the research design One-Group Pretest-Posttest Design. The measuring instrument used in this study is the scale of measurement of internet addiction behavior which consists of 50 items before the validity, and after the validity is obtained valid items number 31 items with validity of 0.381 and reliability of 0.888. And getting the subject of 7 students of SMKN 1 Pekanbaru who were identified as having high levels of internet addiction behavior. The data analysis technique used is non-parametric statistical technique using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. This is known from "Test Statistics", known as Asymp. Sig. (2-tailed) worth 0.017. Because the value of 0.018 is smaller than <0.05, it can be concluded that "Ha is accepted". For this reason, it can be concluded that there is a difference in the score of the behavior of internet addiction before and after being given treatment in the form of self control techniques. Based on the calculations that have been made obtained, the Pre-test 14.3% is in the very high category and 85.7% in the high category. Post-test was 28.6% in the low category and 71.4% in the very low category. Thus Ha is accepted and Ho is rejected. So it can be concluded that there is an effect of the technique of self control on students' internet addiction behavior is equel to 71,7%.Key Words: Self Control, Internet Addiction Behavior